(Whose) value-sensitive design: A study of long-distance relationships in an Arabic cultural context - Alsheikh, Tamara; Rode, Jennifer A.; Lindley, Siân (Proceedings of the 2011 ACM conference on Computer Supported Cooperative Work (CSCW 2011), 2011)
This paper describes a qualitative study of how 11 Arab individuals use technology in the context of their long-distance romantic relationships. Our participants’ communication practices bear similarities to previous findings on the mediation of intimacy in the West, but also highlight key differences. We show how these differences relate to expectations of men and women in Arabic culture, and describe how our participants used technologies to enact conventional roles according to these expectations. We note implications for cross-cultural research and value-sensitive design, demonstrating how our participants’ practices relate to Islamic values of support and protection of women. We apply various analytical lenses, including Islamic feminist theories, in interpreting the data.